2014
DOI: 10.5194/bg-11-3647-2014
|View full text |Cite
|
Sign up to set email alerts
|

Time of emergence of trends in ocean biogeochemistry

Abstract: Abstract. For the detection of climate change, not only the magnitude of a trend signal is of significance. An essential issue is the time period required by the trend to be detectable in the first place. An illustrative measure for this is time of emergence (ToE), that is, the point in time when a signal finally emerges from the background noise of natural variability. We investigate the ToE of trend signals in different biogeochemical and physical surface variables utilizing a multimodel ensemble comprising … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 75 publications
6
108
0
Order By: Relevance
“…Earth system modelling suggested that sea surface pCO 2 and sea surface pH trends could rise beyond the detection threshold already after 12 years from now. DIC trends would become clear after 10-30 years and trends in the sea surface temperature after 45-90 years (Keller et al, 2014). Accordingly, an earlier detection threshold for changes in mean ENSO-induced carbon cycle variability (pCO 2 , pH, biological productivity) than for ocean temperature changes during the 21st century was predicted by Keller et al (2015).…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Earth system modelling suggested that sea surface pCO 2 and sea surface pH trends could rise beyond the detection threshold already after 12 years from now. DIC trends would become clear after 10-30 years and trends in the sea surface temperature after 45-90 years (Keller et al, 2014). Accordingly, an earlier detection threshold for changes in mean ENSO-induced carbon cycle variability (pCO 2 , pH, biological productivity) than for ocean temperature changes during the 21st century was predicted by Keller et al (2015).…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 97%
“…when do trends in key ocean variables emerge as robust on the background of analytical uncertainty and interannual variability? Keller et al (2014Keller et al ( , 2015 provided new insight into this issue. Earth system modelling suggested that sea surface pCO 2 and sea surface pH trends could rise beyond the detection threshold already after 12 years from now.…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 99%
“…In the ocean, Keller et al (2014) have demonstrated that the time of emergence for pCO 2 and pH is about 12 years and ∼10-30 years for DIC, with open-ocean time-series sufficiently long in duration to demonstrate long-term trends (e.g., Bates et al, 2014). Similarly, the Harrington Sound time-series of seawater CO 2 -carbonate chemistry and anomalies from 1996 to 2016 is thus of sufficient length to demonstrate trend emergence and it constitutes one of the longest, if not the longest, coastal ocean time-series in the global coastal ocean.…”
Section: Comparison Of Onshore and Offshore Trends In Seawater Co 2 -mentioning
confidence: 99%
“…4a and b, full range). We estimate when the anthropogenically forced, global mean land and ocean uptake fluxes exceeds the envelope of preindustrial natural variability (Hawkins and Sutton, 2012;Keller et al, 2014). As a threshold criteria, it is required that the decadally smoothed uptake fluxes are larger than the upper bound of 2 standard deviations of the annual fluxes prior to 1750 CE.…”
Section: Carbon Cyclementioning
confidence: 99%